'You've got autism because you like order and you do not look into my eyes': some reflections on understanding the label of 'autism spectrum disorder' from a dishuman perspective. Issue 9 (20th October 2016) - Richards, Michael
Abstract: The psychiatrists and health professionals who 'updated' the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders in 2013 changed how 'autism' is meant to be interpreted. For example, Asperger's disorder merged into an overall collective of 'autism spectrum disorders', rendering Asperger's non-existent as a separate disorder. Yet the terms 'Asperger's', 'autistic' and 'autism', in general, are used on a daily basis by people who have been diagnosed/labelled in this way over the course of their lives, or indeed are used by people to label others in stereotypical and prejudicial ways that leads to their marginalisation. With this thought in mind, the author briefly reflects on his own experiences of being labelled with 'Asperger's' or as being 'autistic' (a label he rejects), whilst thinking from a 'dis/human' perspective, a viewpoint that seeks to unpack and challenge the dominant concepts of what it means to be human in the twenty-first century. While it is difficult to avoid being labelled in ways that lead to discrimination and rejection, a dishuman perspective offers a viewpoint against the narrow versions of what it means to be human, relating to how disability can trouble the notion of what it means to be human and indeed inform the very meaning of what it means to be human.